Analisis Proposi Dewan Komisaris Independen, Ukuran Dewan Direksi, Komite Audit, Blockholder Ownership terhadap Kinerja Keuangan - Nanik Septiana; Muhammad Abdul Aris (Jurnal Akuntansi, Keuangan, dan Manajemen, 2023)
Purpose: aims to analyze the elements the financial performance of banking on the Indonesia Stock Exchange for the 2017-2020 period. Methodology: This type of research is quantitative research using secondary data in the form of annual reports. This study used a sample of 138 banks for four years. The analysis used is multiple linear regression, classical assumption test, t test and F test using SPSS 25 program. Results: The results of this study indicate that the proportion of independent commissioners, audit committees, and blockholder ownership does not affect the financial performance of banks, while the size of the board of directors affects the financial performance of banks. Limitations: The obstacle of this research is that it focuses on the financial sector, companies disclose financial statements in rupiah and time constraints. Contribution: This research is expected to be able to share an explanation for shareholders and companies to determine the variables that affect financial performance.